2018
DOI: 10.1097/md.0000000000013241
|View full text |Cite
|
Sign up to set email alerts
|

Association of exposure level to passive smoking with hypertension among lifetime nonsmokers in Japan: a cross-sectional study

Abstract: Brief exposure to passive smoking immediately elevates blood pressure. However, little is known about the association between exposure to passive smoking and chronic hypertension. We aimed to examine this association in a cross-sectional study, after controlling multiple potential confounders.Participants included 32,098 lifetime nonsmokers (7,216 men and 24,882 women) enrolled in the Japan Multi-Institutional Collaborative Cohort Study. Passive smoking was assessed using a self-administered questionnaire. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…In our report, we found PSE increased odds of hypertension which is in tandem with similar reports on the contribution of PSE to hypertension [ 24 28 ] and cardiovascular events [ 13 , 20 , 25 , 29 , 30 ]. According to similar reports from other populations, PSE independently increased the risk of hypertension by 11% in a Japanese population [ 24 ], 16% in among Korea adults [ 26 ] and 38% among Chinese women [ 27 ]. Similarly, PSE accounted for about 379,000 ischaemic heart disease-related mortality among adults worldwide in 2004 [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our report, we found PSE increased odds of hypertension which is in tandem with similar reports on the contribution of PSE to hypertension [ 24 28 ] and cardiovascular events [ 13 , 20 , 25 , 29 , 30 ]. According to similar reports from other populations, PSE independently increased the risk of hypertension by 11% in a Japanese population [ 24 ], 16% in among Korea adults [ 26 ] and 38% among Chinese women [ 27 ]. Similarly, PSE accounted for about 379,000 ischaemic heart disease-related mortality among adults worldwide in 2004 [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, a recent report by Xu and colleagues [ 44 ] found PSE significantly increased the risk of AAC among women but not among men in China. However, Kim et al [ 26 ] and Tamura et al [ 24 ] in two separate studies from South Korea and Japan respectively found PSE increased the odds of hypertension independent of sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…The population of respondents who were exposed to cigarette smoke (aged≥24.29 or <24.29 years) and experienced hypertension was about 44.20% of the population, and the population of respondents who were exposed to cigarette smoke (aged<24.29 years) and experienced hypertension was around 25.70% of the population (Mustolih, Trisnawati, & Ridha, 2015). These results were not in line with the study carried out by (Tamura et al, 2018), which suggested that exposure to cigarette smoke was related to the incidence of hypertension. This difference in findings from both the above research studies serves as the background for carrying out this research.…”
Section: Introductioncontrasting
confidence: 61%
“…One of them being an increase in blood pressure or hypertension. This can be explained by several biological effects caused by the exposure to cigarette smoke in passive smokers, e.g., vasoconstriction mediated by nicotine-induced catecholamine release, endothelial dysfunction, and decreased production of nitric oxide (Tamura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Height and weight were measured directly on the day of the survey; body mass index (BMI) was calculated as weight in kilograms divided by the square of height in meters (kg/m 2 ). Each participant’s blood pressure was measured by a nurse or trained staff during health checks, using an automated blood pressure measurement monitor, with the patient in a seated position 38 .…”
Section: Methodsmentioning
confidence: 99%